GE_GERICHTE C/6928/2018 vom 2. Oktober 2018 - GE Cour de justice (2018)
FAILLITE SANS POURSUITE PRÉALABLE ; RECONNAISSANCE DE DETTE ; BAIL À LOYER; LOCAL PROFESSIONNEL ; INSOLVABILITÉ | LP.82.al1; LP.190.al1.ch2